A Porous Organic Polymer Nanotrap for Efficient Extraction of Palladium. Issue 44 (9th June 2020) - Aguila, Briana; Sun, Qi; Cassady, Harper C.; Shan, Chuan; Liang, Zhiqiang; Al‐Enizic, Abdullah M.; Nafadyc, Ayman; Wright, Joshua T.; Meulenberg, Robert W.; Ma, Shengqian
Abstract: To offset the environmental impact of platinum‐group element (PGE) mining, recycling techniques are being explored. Porous organic polymers (POPs) have shown significant promise owing to their selectivity and ability to withstand harsh conditions. A series of pyridine‐based POP nanotraps, POP‐Py, POP‐ p NH2 ‐Py, and POP‐ o NH2 ‐Py, have been designed and systematically explored for the capture of palladium, one of the most utilized PGEs. All of the POP nanotraps demonstrated record uptakes and rapid capture, with the amino group shown to be vital in improving performance. Further testing on the POP nanotrap regeneration and selectivity found that POP‐ o NH2 ‐Py outperformed POP‐ p NH2 ‐Py. Single‐crystal X‐ray analysis indicated that POP‐ o NH2 ‐Py provided a stronger complex compared to POP‐ p NH2 ‐Py owing to the intramolecular hydrogen bonding between the amino group and coordinated chlorine molecules. These results demonstrate how slight modifications to adsorbents can maximize their performance. Abstract : Green mining for palladium : As an alternative to platinum‐group element (PGE) mining, a series of porous organic polymer nanotraps were rationally designed for their ability to recover Pd from aqueous solutions as a potential recycling method. Through intramolecular hydrogen bonding, the adsorbent–Pd complex could be stabilized, allowing for selective capture of Pd under environmentally relevant conditions.